C4. Maternal cardiac changes during uncomplicated twin pregnancy: does the chorionicity matter?. (12th August 2016) - Ghi, T.; Franchi, L.; Fieni, S.; Dall'Asta, A.; Gaibazzi, N.; Siniscalchi, C.; Pedrazzi, G.; Sciatti, E.; Bonadei, I.; Vizzardi, E.; Montaguti, E.; Degli Esposti, D.; et al.
Abstract: Objectives : To assess longitudinally the echocardiographic findings in a cohort of women carrying an uncomplicated monochorionic (MC) twin pregnancy and compare them with those obtained from dichorionic (DC) twin gestations. Methods : Healthy women with MC twin pregnancies were submitted to serial transthoracic maternal echocardiography during the first, second and third trimester. Cases with severe obstetric complications after enrollment were eventually excluded. The cardiac findings obtained at different time frames within the MC group were compared. Moreover, these data were compared with those obtained longitudinally in a cohort of uncomplicated DC twin pregnancies. Results : From 2012 to 2016, 19 women with an uncomplicated MC twin pregnancy were included in this study group. Among this group no significant changes were documented from 1st to 3rd trimester with the exception of an ejection fraction decrease. In respect of 48 DC uneventful twin gestations in the MC set the following significant differences were observed: reduced cardiac output (midtrimester) and ejection fraction (1st and 2nd trimester), increased total vascular resistance (1st trimester). Regarding the diastolic function in the MC versus DC twins a significant increase of the following parameters was noted: mitral valve E/A (early diastolic – atrial contraction) ratio (3rd trimester); MSE1 (1st and 2nd trimester), MS E1/A1 (3rd trimester); ML E1 (2nd and 3rd trimester); ML E1/A1 (3rd trimester). The longitudinal trend of the following data showed a significant difference between the MC and the DC set: increase of ML E1 and MLE1/A1, decrease of ML A1. Conclusions : In uncomplicated MC twin pregnancies maternal cardiac changes seem to differ significantly from the DC set. In particular, in the former group the diastolic function impairment is less pronounced presumably due to the lower circulating volume.